tRF-AspGTC Promotes Intracranial Aneurysm Formation by Controlling TRIM29-Mediated Galectin-3 Ubiquitination - Chao Wang; Bing Yu; Han Zhou; Huanting Li; Shifang Li; Xiaolu Li; Wentao Wang; Yugong Feng; Tao Yu (Research)
Transfer RNA-derived small RNAs, a recently identified class of small noncoding RNAs, play a crucial role in regulating gene expression and are implicated in cerebrovascular diseases. However, the specific biological roles and mechanisms of transfer RNA-derived small RNAs in intracranial aneurysms (IAs) remain unclear. In this study, we identified that the transfer RNA-Asp-GTC derived fragment (tRF-AspGTC) is highly expressed in the IA tissues of both humans and mice. tRF-AspGTC promotes IA formation by facilitating the phenotypic switching of vascular smooth muscle cells, increasing of matrix metalloproteinase 9 expression, and inducing of oxidative stress and inflammatory responses. Mechanistically, tRF-AspGTC binds to galectin-3, inhibiting tripartite motif 29-mediated ubiquitination and stabilizing galectin-3. This stabilization activates the toll-like receptor 4/MyD88/nuclear factor kappa B pathway, further driving phenotypic switching and inflammation. Clinically, circulating exosomal tRF-AspGTC demonstrates strong diagnostic efficacy for IAs and is identified as an independent risk factor for IA occurrence. These findings highlight the potential of tRF-AspGTC as a promising diagnostic biomarker and therapeutic target for IAs.